LEARNING VIRTUAL ENVIRONMENTS AS MEDIATION INSTRUMENT - Suárez Guerrero, Cristóbal (2014)
There is a theoretical need for the pedagogical analysis, the presence and use of the New Information and Communication Technologies in the educational processes, this article proposes to recognize, from a sociocultural perspective, the Virtual Environments of Learning as an instrument of mediation. This means, as a component adding to the educational activity two orientations: as structure of external action and as a source for internal representation. Formulated in this way, a virtual learning environment orients itself towards proper ways of technological performance in the educational process. Simultaneously this triggers in students, new forms of cognitive regulation that offer new opportunities and strategies as a condition of learning. This perspective is part of the pedagogic dimension necessary for a pertinent application and orientation of learning in virtual trainning.